An optimised electrochemical biosensor for the label-free detection of C-reactive protein in blood - Bryan, Thomas; Luo, Xiliang; Bueno, Paulo Roberto [UNESP]; Davis, Jason J. (Elsevier, 2013)
C-reactive protein (CRP) is an acute phase protein whose levels are increased in many disorders. There exists, in particular, a great deal of interest in the correlation between blood serum levels and the severity of risk for cardiovascular disease. A sensitive, label-free, non-amplified and reusable electrochemical impedimetric biosensor for the detection of CRP in blood serum was developed herein based on controlled and coverage optimised antibody immobilization on standard polycrystalline gold electrodes. Charge transfer resistance changes were highly target specific, linear with log. CRP. concentration across a 0.5-50. nM range and associated with a limit of detection of 176. pM. Significantly, the detection limits are better than those of current CRP clinical methods and the assays are potentially cheap, relatively automated, reusable, multiplexed and highly portable. The generated interfaces were capable not only of comfortably quantifying CRP across a clinically relevant range of concentrations but also of doing this in whole blood serum with interfaces that were, subsequently, reusable. The importance of optimising receptor layer resistance in maximising assay sensitivity is also detailed. © 2012.
Keywords: Biosensor; Blood; C-reactive protein; Electrochemical impedance spectroscopy; Resistance; Self-assembly; Acute phase proteins; Antibody immobilization; Blood serum; C-reactive proteins; Cardio-vascular disease; Charge transfer resistance; Clinical methods; Detection limits; Electrochemical biosensor; Highly-portable; Label free; Label-free detection; Limit of detection; Polycrystalline gold; Receptor layers; Whole blood; Assays; Charge transfer; Chemical detection; Electric resistance; Proteins; Self assembly; Biosensors; C reactive protein; polyclonal antibody; biosensor; blood analysis; controlled study; electric resistance; electrochemical detection; electrochemical impedance spectroscopy; human; laboratory automation; limit of detection; process development; process optimization; protein blood level; protein determination; protein immobilization; quantitative analysis; sensitivity and specificity; validation process; Biosensing Techniques; C-Reactive Protein; Cardiovascular Diseases; Dielectric Spectroscopy; Humans; Immunoassay; Limit of Detection; Serum